Emerging Unit Trust Industry In Malaysia: The Performanceof Unit Trust Funds - Heng, Lem Tien (2004)
This research aims to study the performance of unit trusts investment in the context of Malaysia unit trust industry. In order to find out the performance of unit trust funds, the return and risk analyses are done on selected equity unit trust funds offered by one of the major unit trsut companies in Malaysia.